2019
DOI: 10.1172/jci.insight.126345
|View full text |Cite
|
Sign up to set email alerts
|

ROR1-CAR T cells are effective against lung and breast cancer in advanced microphysiologic 3D tumor models

Abstract: Conflict of interest: MH is an inventor on patents related to chimeric antigen receptor technologies that have been filed by the Fred Hutchinson Cancer Research Center

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 44 publications
(64 reference statements)
0
111
0
Order By: Relevance
“…The development of microphysiologic 3D tumor models and their use with CAR T-cells has been described. 10 In brief, collagen scaffolds derived from decellularized porcine gut were fixed in cell crowns and placed in 12-well plates, each well with 2.5 mL medium. 1×10 5 MDA-MB-231_ffluc cells were seeded on the luminal side of the scaffold and cultured for 11 days with complete medium exchanges every 2-3 days and immediately prior to T-cell treatment.…”
Section: Microphysiologic 3d Tumor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of microphysiologic 3D tumor models and their use with CAR T-cells has been described. 10 In brief, collagen scaffolds derived from decellularized porcine gut were fixed in cell crowns and placed in 12-well plates, each well with 2.5 mL medium. 1×10 5 MDA-MB-231_ffluc cells were seeded on the luminal side of the scaffold and cultured for 11 days with complete medium exchanges every 2-3 days and immediately prior to T-cell treatment.…”
Section: Microphysiologic 3d Tumor Modelmentioning
confidence: 99%
“…We sought to evaluate the combination treatment of ROR1-CAR T-cells with SD-208 in a microphysiologic 3D TNBC model (10). In this model, T-cells have to combat a large tumor cell mass and tumor regression can be monitored by BLI over a several-day period.…”
Section: Enhanced Potency Of Ror1-car T-cells In Combination With Tgfmentioning
confidence: 99%
“…In recent years, ROR1 has emerged as a molecule of substantial interest for the development of targeted therapy including mAbs [15], chimeric antigen receptor T-cells (CAR-T) [39,40], bi-specific T-cell engager (BiTE) [41] and SMIs targeting the cytoplasmic tyrosine kinase domain (TKI) [29,42] as well as the extracellular part of ROR1 [43,44]. The common characteristics for these compounds are that effects on signaling are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the microphysiological 3D lung cancer and breast cancer models have been created to investigate the antitumor activity of receptor tyrosine kinase‐like orphan receptor 1 (ROR1)‐specific CAR‐T cells, in which the decellularized submucosa and mucosa of porcine jejunum was used as the ECM scaffold for culturing A549 nonsmall cell lung cancer cells and MDA‐MB‐231 cells under static or dynamic culture conditions. [ 160 ] It was demonstrated that the ROR1‐CAR T cells rapidly infiltrated and migrated through the 3D tumor tissues and exhibited a potent antitumor effect, as shown by the secretion of caspase‐cleaved keratin 18, a tumor cell apoptotic marker. Similarly, a 3D microfluidic human ovarian cancer model was developed by embedding human epidermal growth factor receptor 2 (HER2) + ovarian cancer cells (SKOV3) in a micropatterned gelatin methacryloyl (GelMA) hydrogel and micromilled hypoxia device to establish an oxygen gradient across micropatterned cancer cells.…”
Section: Other Relevant Immunocompetent Ooc Modelsmentioning
confidence: 99%